Issledovanie kinematicheskoi struktury top-spinov v tennisse - Zaitsev, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of this study was to analyze the kinematic structure of the strong top-spines in the elite tennis-players of our country. It had been stated that the phase of a drive when top-spine's performing is characterized by the significant positive vertical acceleration (61±12,7 m/s2). The tennis-players use the optimal speed of a ball to ensure the more accuracy, assurance and stability of shots. The motor actions of a tennis-player are to posess an adequate adaptive changeability.